2011
DOI: 10.1089/end.2010.0554
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Trial Comparing Immediate Versus Delayed Ureteroscopy for Patients with Ureteral Calculi and Normal Renal Function Who Present to the Emergency Department

Abstract: In our experience, emergency ureteroscopy showed equal efficacy and safety compared with the elective procedure. It has the main advantage of providing both immediate relief from pain and stone fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…Both studies have strongly recommended the emergency URS approach. 28,31 Failure rates ranged from 6.5% to 10% in both studies. The use of stents was also popular.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Both studies have strongly recommended the emergency URS approach. 28,31 Failure rates ranged from 6.5% to 10% in both studies. The use of stents was also popular.…”
Section: Discussionmentioning
confidence: 85%
“…Higher use of double-J stents was reported in the elective surgery group (80% vs. 19.4%). 31 Our study has its limitations. It is retrospective and not controlled.…”
Section: Discussionmentioning
confidence: 89%
“…The definition of emergency varied among the studies from 12 to 48 h from admission to the emergency room. Stone-free status was defined on postoperative imaging (KUB in 3 studies and CT scan in one), which was done at 1 month in most studies (Table 1) [16][17][18][19]. In six studies (4 prospective randomized controlled and 2 retrospective case-control studies), emergent ESWL (n = 356) was compared to delayed ESWL (n = 355).…”
Section: Resultsmentioning
confidence: 99%
“…Al Ghazo et al stratified their 244 cases by stone location, and they found higher stone-free rates for mid (95.8%) and distal ureter (96.6%) compared to distal (69.4%) [30]. Conversely, in the only randomized trial comparing emergent versus delayed URS, Guercio et al found that neither stone size nor location had any impact on stone-free rate [17]. This finding could be explained by the fact that this was the only group to use a flexible scope (besides the semirigid one), and therefore one might expect that a more aggressive pursuit of residual or migrated fragments was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the following factors: failure after a trial of medical expulsion therapy (MET) would lead to the clinical decision for emergency ureteroscopy; the median waiting time for emergency surgery was 26h; and most patients would stay an additional day post-surgery for symptom monitoring before they are discharged. In contrast, EL is performed as Day Surgery procedures [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%